Pengaruh arah aliran input resin sintetis pada proses vacuum infusion resin terhadap kekuatan tarik komposit serat kulit waru (hibiscus tiliaceus) - Deky Framasta; Akhmad Farid; Nova R. Ismail; Arief Rizki Fadhillah (TURBO [Tulisan Riset Berbasis Online], 2021)
The use of natural fibers as a reinforcing material or reinforcement in composite materials has long been developed. Natural fibers are good environmentally materials in the development of engineering materials. Good environmentally materials are materials that, when used and disposed of, do not have the potential to damage the environment and harm health. Natural fibers have different characteristics and properties for each type. The bark fibers of the hibiscus tree (hibiscus tiliaceus) can also be seen as the characteristics of several factors that affect the tensile strength. This study aims to analyze the fault by knowing the direction of flow of synthetic resin input with the vacuum infusion resin method using the bark fiber of the hibiscus tree and bisphenol resin to tensile strength. The bark of the hibiscus tree was treated with 6% NaOH immersion for 120 minutes. And variations in the direction of resin flow input 1 In 1 Out, 2 In 1 Out and 4 In 1 Out. The resin used is Bisphenol. The result of the tensile test is the variation of the flow direction of 2 In 1 Out, the highest tensile stress value is 328.18 MPa, the lowest tensile stress is the variation in the flow direction of 4 In 1 Out with a value of 271.17 MPa. The fault model of all variations in the flow direction is multiple areas, as well as fiber pull out in the 1 In 1 Out and 4 In 1 Out flow directions. For 2 In 1 Out delamination fault mode.Keywords: Composite, hibiscus bark fiber, resin flow direction, vaccum infusion resin.